Analisis Pengelolaan Sampah di Kawasan Wisata Ancol untuk Mendukung Pariwisata Berkelanjutan - Sutrisno, Bambang; Sasaerila, Hidayat Yorianta; Nurhasanah, Nunung (Universitas Al Azhar Indonesia, 2025)
Effective waste management is a key prerequisite for achieving sustainable tourism. Sustainable tourism provides important benefits such as environmental conservation, improved community well-being, and economic contributions to destinations. This study aims to analyze the existing waste management system in the Ancol tourism area, identify the challenges faced, and formulate recommendations for its optimization. The analysis focuses on the waste management system at the Integrated Waste Processing Facility (TPST) Ancol, Jakarta, with reference to national regulations (Law No. 18/2008, Jakarta Governor Regulations No. 102/2021 and No. 142/2019) and the Global Sustainable Tourism Council (GSTC) standards. A descriptive qualitative approach was applied through observations, interviews, and document analysis. The results show that TPST Ancol has implemented four-stream waste segregation and circular economy-based processing, such as composting for parks and sorting recyclable waste for waste banks. However, challenges remain in terms of limited visitor participation in source segregation, constraints in human resources, and inadequate technological infrastructure. The Soft Systems Methodology (SSM) analysis highlights the importance of visitor education, infrastructure improvement, and multi-stakeholder collaboration to strengthen the triple bottom line (people, planet, profit). This study recommends optimizing monitoring systems, enforcing stricter environmental policies, and integrating educational programs to position Ancol as a world-class sustainable tourism destination.Keywords - Ancol, Soft Systems Methodology, Sustainability, Tourism, Waste.